Uganda - Information Technology and Rural Development : The Nakaseke Multi-Purpose Telecenter - Prakash, Siddhartha (World Bank, Washington, DC, 2012)
While often modern technology tends to bypass local communities in remote regions, recent technological advancements in communications have erased geographical distances, and infra-structural bottlenecks: located in some fifty kilometers north of Kampala, Uganda, in a remote village, the Nakaseke Multi-purpose Community Tele-center, has introduced new information, and communication technologies to this rural area, and catalyzed a number of development activities in the region. The Tele-center is part of a chain of five donor supported Tele-center projects in Africa, whose overall objective is to stimulate rural development, by facilitating access to information, learning resources, and communication technologies by the Nakaseke, and Kasangombe communities, and to support improved medical services through telemedicine. The early involvement of the communities, helped mainstream Tele-center issues into community activities, by localizing its applications to an understandable level for the communities. Nakaseke is a successful example of transferring the maintenance costs from donors, to the local communities, thereby moving towards sustainable local ownership. Among its challenges, the development of a framework for information dissemination, sharing, and networking is in the process, by forging practical linkages within information communication technology initiatives in, and outside the country.